Phaedras Brief an Hippolytus: Ovids Brief (Her. 4) in der römischen bildenden Kunst - Gesztelyi, Tamás (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
Euripides has Paedra write a letter to Theseus in which she accuses Hippolytus of raping her. In the Heroides, Ovid has Phaedra write a letter to Hippolytus which describes her burning love for the young man. In Roman visual arts the story is usually depicted as a nurse handing over a letter to Hippolytus, which he declines. It seems obvious to identify this letter with the one composed by Ovid, i.e., it is this letter that found its way into the visual arts. The contents of the love letter gradually overshadowed the tragic outcome of the story: they represented endless spousal love in sepulchral art.